Visual assessment of mitotic figures in breast cancer: a comparative study between light microscopy and whole slide images. Issue 6 (22nd September 2021) - Lashen, Ayat; Ibrahim, Asmaa; Katayama, Ayaka; Ball, Graham; Mihai, Raluca; Toss, Michael; Rakha, Emad
Abstract : Background and aims: Visual assessment of mitotic figures in breast cancer (BC) remains a challenge. This is expected to be more pronounced in the digital pathology era. This study aims to refine the criteria of mitotic figure recognition, particularly in whole slide images (WSI). Method and results: Haematoxylin and eosin (H&E)‐stained BC sections ( n = 506) were examined using light microscopy (LM) and WSI. A set of features for identifying mitosis in WSI and to distinguish true figures from mimickers was developed. Changes in the mitotic count between the two platforms was explored. Morphological features of mitoses were recorded separately, including absence of nuclear membrane, chromatin hairy‐like projections, shape, cytoplasmic features, mitotic cell size and relationship to surrounding cells. Each mitotic phase has its own mimickers. Fifty‐eight per cent of mitoses showed absent hairy‐like projection in WSI; however, 89% retained their ragged nuclear border, which distinguished them from mimickers including apoptotic cells, lymphocytes and dark elongated hyperchromatic structures. Mitosis in WSI showed loss of fine details, and there was a 20% average reduction rate of mitotic counts when compared to the same area on LM. Using refined mitosis recognition criteria in WSI resulted in a twofold improvement of interobserver concordance. However, when compared to LM, 19% of cases were underscored in WSIs. Conclusions: All morphological features of mitosis should be considered to enable recognition and differentiation from their mimickers, particularly in WSI, to ensure reliable BC grading. Refining mitotic cut‐offs per specific area when using WSI, based on the degree of reduction and association with outcome, is warranted. Abstract :